Down-regulation of NOX4 by Betulinic Acid Protects against Cerebral Ischemia-reperfusion in Mice - 鲁佩;张琛琛;张晓敏;李会革;罗爱林;田玉科;徐卉 (Current medical science, 2017)
Ischemic stroke leads to high potentiality of mortality and disability. The current treatment for ischemic stroke is mainly focused on intravenous thrombolytic therapy. However, ischemia/reperfusion induces neuronal damage, which significantly influences the outcome of patients with ischemic stroke, and the exact mechanism implicated in ischemia/reperfusion injury remains unclear, although evidence shows that oxidative stress is likely to be involved. Betulinic acid is mainly known for its anti-tumor and anti-inflammatory activities. Our previous study showed that betulinic acid could decrease the reactive oxygen species（ROS） production by regulating the expression of NADPH oxidase. Thus, we hypothesized that betulinic acid may protect against brain ischemic injury in the animal model of stroke. Focal cerebral ischemia was achieved by using the standard intraluminal occlusion method and reperfusion enabled after 2 h ischemia. Neurological deficits were scored. Infarct size was determined with 2,3,5-triphenyltetrazolium chloride monohydrate（TTC） staining and the mRNA expression of NADPH oxidase 4（NOX4） was determined by RT-PCR in infarct tissue. ROS generation and apoptosis in ischemic tissue were analyzed by measuring the oxidative conversion of cell permeable 2＇,7＇-dichloro-fluorescein diacetate（DCF-DA） to fluorescent dichlorofluorescein（DCF） in fluorescence microplate reader and TUNEL assay, respectively. In Kunming mice, 2 h of middle cerebral artery（MCA） occlusion followed by 24 or 72 h of reperfusion led to an enhanced NOX4 expression in the ischemic hemisphere. This was associated with elevated levels of ROS generation and neuronal apoptosis. Pre-treatment with betulinic acid（50 mg/kg/day for 7 days via gavage） prior to MCA occlusion prevented the ischemia/reperfusion-induced up-regulation of NOX4 and ROS production. In addition, treatment with betulinic acid could markedly blunt the ischemia/reperfusion-induced neuronal apoptosis. Finally, betulinic acid reduced infarct volume and ameliorated the neurological deficit in this stroke mouse model. Our results suggest that betulinic acid protects against cerebral ischemia/reperfusion injury in mice and the down-regulation of NOX4 may represent a mechanism contributing to this effect.